Construction for fluid flows of tangent spherical indicatrix by flows - Körpınar, Talat; Asıl, Vedat (Boletim da Sociedade Paranaense de Matematica, 2020)
In this article, we obtain the characterizations of tangent spherical indicatrix by inextensible flows in space. Moreover, we obtain some performances for curvatures of a tangent spherical indicatrix. © Soc. Paran. de Mat.
Keywords: Curvatures; Inextensible flows; Tangent spherical image